CONSTRUCTED (HI)STORIES (Philological Studies, 2022)
The aim of this paper is to analyze the novel Solovyov and Larionov by the contemporary Russian writer Evgeny Vodolazkin through the prism of interdiscursive relations of novel-history/ historiography. Starting from the theories of the postmodernist historical novel (Elizabeth Wesseling, Brian McHale, Linda Hutchon), the interpretation is focused on one of the dominant aspects of this literary genre - the immanent provocation of the relationship between fiction and history that is realized in multiple ways: through affirmation of their common narrative aspects, through epistemological problematizations of historical knowledge and truth and by illustrating the mediated availability of the past through its textual traces.
Keywords: postmodernist historical novel, history-literature relation, narrative, epistemological skepticism, Evgeny Vodolazkin.